Enantioselective organocatalytic Michael addition of malonate esters to nitro olefins using bifunctional cinchonine derivatives. - Ye, J; Dixon, D; Hynes, P (2005)
A family of 9-amino(9-deoxy) epicinchonine derivatives, possessing a range of mono- and bidentate hydrogen bond donor groups at the 9-position, were synthesised and evaluated for asymmetric organocatalytic activity in the dimethyl malonate Michael addition to beta-nitrostyrene; thiourea derivative was identified as the most effective bifunctional organic catalyst and found to induce high enantioselectivity in the malonate ester Michael addition reaction to a range of nitro olefins.